Metabolic Concepts in Idiopathic Intracranial Hypertension and Their Potential for Therapeutic Intervention. Issue 4 (December 2018) - Hornby, Catherine; Mollan, Susan P.; Botfield, Hannah; O'Reilly, Michael W.; Sinclair, Alexandra J.
Abstract : Background: Traditional risk factors associated with idiopathic intracranial hypertension (IIH) include obesity, weight gain, and female sex. The incidence of IIH is increasing and yet the underlying trigger and the fueling pathological mechanisms are still poorly understood. Evidence Acquisition: Review of ophthalmology, neurology, general surgery, obesity, endocrinology, nutrition, and neurosurgery literature was made. Results: The facts that implicate sex and obesity in IIH and headache are examined. The role of fat distribution in IIH is questioned, and the concept of adipose tissue functioning as an endocrine organ driving IIH is discussed. The impact of androgen metabolism in IIH is reviewed as is the emerging role of glucagon-like-peptide-1 analogues in modulating intracranial pressure. This introduces the concept of developing targeted disease-modifying therapeutic strategies for IIH. Conclusions: This review will discuss the possible role of the adipose/gut/brain metabolism axis in IIH and speculate how this may impact the pathogenesis of IIH and therapeutic opportunities.